South African Rural Girls' Safety Strategies on the School Journey. Issue 1 (1st March 2023) - Ngidi, Ndumiso Daluxolo; Ntinga, Xolani; Khumalo, Ayanda; Essack, Zaynab
Abstract: In this article, we use data generated through photovoice and focus group discussions to examine how primary school girls from two resource-poor and high-risk rural communities in KwaZulu-Natal, South Africa, negotiate their safety on the dangerous journey to and from school. Our findings show that girls actively identify and apply specific safe-seeking strategies by drawing on available community and interpersonal resources as they navigate their way to school. These strategies moderate risk exposure and are perceived to reduce girls' vulnerability to victimization. While the sustainability of these strategies remains in question, it is essential to note that girls can exercise their agency in providing safety in sociocultural and geographic contexts that expose them to risk.